Geschlechterreflektierte Pädagogik gegen Rechts. - Hechler, Andreas (Verlag Barbara Budrich, 2015)
Anyone who deals with neo-Nazi prevention must consider the category of gender, because gender is a core aspect of neo-Nazi ideology and life. The contributions examine this point of view as well as the pedagogical and theoretical practices of the triad gender - pedagogy - neo-Nazism. The authors make it clear that prevention of neo-Nazism must be streamed just as much as gender-reflected pedagogy.